Circle solutions for student wellbeing - Roffey, Sue (SAGE, 2014)
Revised new edition of Circle Time for Emotional Literacy that illustrates how the Circle Solutions philosophy and pedagogy can be used in all phases of education to build relationships and resillience for children and young people.